Dosis de guano de isla y su efecto en la propagación en bolsas del Capsicum sp. "ají charapita" en Zungarococha, Loreto - 2023 - Chashnamote Salazar, Arnulfo (2023)
The supply of quality seedlings of Capsicum sp. "Ají Charapita" so that the farmer achieves his goals of higher fruit yields, the Faculty of Agronomy of the National University of the Peruvian Amazon, has been studying this possibility with the following research work: DOSE OF ISLAND GUANO AND ITS EFFECT ON THE PROPAGATION IN BAGS OF Capsicum sp. "AJI CHARAPITA" IN ZUNGAROCOCHA, LORETO - 2023. With a Complete Random Design with four treatments and four repetitions, the treatments under study were: T0 (Control), T1 (5% island guano), T2 (10% island guano) and T3 (15% island guano) obtaining the following results: That the higher the dose of island guano in the substrate, the variables under study increase their values. Regarding height, crown diameter and basal diameter of the plant, the highest result was obtained by treatment T3 (15% island guano), with 58.95 centimeters, 44.73 centimeters and 5.93 millimeters respectively. Regarding root length and plant root weight, the highest result was obtained by treatment T3 (15% island guano), with 25.41 centimeters and 10.21 grams respectively.